Perancangan dan Implementasi Sistem Informasi Perpustakaan berbasis Web (Studi Kasus : SMP Masehi Pekalongan) - Yuvika Sahid Saputri; Radius Tanone (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
The library in SMP Masehi Pekalongan did not well manage and not yet computerized. Based on these problems, this research aims to design and create a library-based information system website in SMP Masehi Pekalongan. The research method used is waterfall development model, which consists of analysis, design, implementation, and testing. The development of this information system uses the Codeigniter framework for system functions because it has high benchmarks, good performance, and works based on the basic concepts of MVC (Model, View, Controller) making it easier to manage the system. The result of this research is a web-based library information system. The system has two users namely admin and students where each user has features in accordance with the permissions they have. Librarians can create and manage book data reports ranging from book lending, book data, and other book information. Data processing in the library becomes easier because it uses library information system.